Factors influencing team performance: What can support teams in high-performance sport learn from other industries? A systematic scoping review - Salcinovic, B.; Drew, M.; Dijkstra, P.; Waddington, G.; Serpell, B. G. (Sports Medicine - Open, 2022)
Background The primary aim of our systematic scoping review was to explore the factors influencing team function and performance across various industries and discuss findings in the context of the high-performance sport support team setting. These outcomes may also be used to inform future research into high-performance teamwork in sport.